2022
DOI: 10.3892/mmr.2022.12863
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of deubiquitinating enzyme USP25 promotes the development of allergic rhinitis by enhancing TSLP signaling in the nasal epithelium

Abstract: Ubiquitin-specific peptidase 25 (USP25) is a key deubiquitylase belonging to the USP superfamily that is primarily involved in inflammation and the immune response. Thymic stromal lymphopoietin (TSLP) is an epithelial-derived cytokine that is regarded as the master switch that initiates and maintains the type 2 immune response in allergic rhinitis (AR). However, the molecular mechanisms by which USP25 regulates TSLP signaling in the nasal epithelium in AR remain unclear. The present study assessed the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…In allergic rhinitis, TSLP plays a central role in the initiation and persistence of allergic responses. The histamine H4 receptor regulates TH2-cytokine profile through TSLP in nasal allergy and the ubiquitin-specific peptidase 25 (USP25) downregulation involved in inflammation and the immune responses enhances the TSLP signalling in the nasal epithelium via decreased expression of TNF receptor-associated factor 3 (TRAF3), thereby exacerbating inflammation in allergic rhinitis [ 80 ]. Recently it was reported that inhibition of TSLP using tezepelumab increases the efficacy of subcutaneous allergen immunotherapy in patients with allergic rhinitis to cats and may promote tolerance after a one-year course of treatment [ 81 ].…”
Section: Tslp In Asthma Nasal Polyposis Allergic Rhinitis and Ocular ...mentioning
confidence: 99%
“…In allergic rhinitis, TSLP plays a central role in the initiation and persistence of allergic responses. The histamine H4 receptor regulates TH2-cytokine profile through TSLP in nasal allergy and the ubiquitin-specific peptidase 25 (USP25) downregulation involved in inflammation and the immune responses enhances the TSLP signalling in the nasal epithelium via decreased expression of TNF receptor-associated factor 3 (TRAF3), thereby exacerbating inflammation in allergic rhinitis [ 80 ]. Recently it was reported that inhibition of TSLP using tezepelumab increases the efficacy of subcutaneous allergen immunotherapy in patients with allergic rhinitis to cats and may promote tolerance after a one-year course of treatment [ 81 ].…”
Section: Tslp In Asthma Nasal Polyposis Allergic Rhinitis and Ocular ...mentioning
confidence: 99%